2022
DOI: 10.1002/ab.22060
|View full text |Cite
|
Sign up to set email alerts
|

Intensity, intent, and ambiguity: Appraisals of workplace ostracism and coping responses

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…that can replace more aggressive responses such as retaliation. While there has been an increasing number of studies that look at people’s coping strategies and how they relate to workplace mistreatment (e.g., Cortina & Magley, 2009; Meral et al, 2022; Salin et al, 2014; Vranjes et al, 2021, 2022; Wang & Wang, 2017), these studies have generally focused on between-person differences in coping strategies and thus have adopted a trait-like approach to coping as an individual difference variable. Yet, people apply a variety of coping strategies throughout a day (Tennen et al, 2000), and have been found to alter their coping strategies based on how successful these strategies are in helping them mitigate their daily stressors (Blaxton & Bergeman, 2017).…”
Section: Future Research Regarding the Mistreatment Dynamicmentioning
confidence: 99%
“…that can replace more aggressive responses such as retaliation. While there has been an increasing number of studies that look at people’s coping strategies and how they relate to workplace mistreatment (e.g., Cortina & Magley, 2009; Meral et al, 2022; Salin et al, 2014; Vranjes et al, 2021, 2022; Wang & Wang, 2017), these studies have generally focused on between-person differences in coping strategies and thus have adopted a trait-like approach to coping as an individual difference variable. Yet, people apply a variety of coping strategies throughout a day (Tennen et al, 2000), and have been found to alter their coping strategies based on how successful these strategies are in helping them mitigate their daily stressors (Blaxton & Bergeman, 2017).…”
Section: Future Research Regarding the Mistreatment Dynamicmentioning
confidence: 99%